Escores visuais e associação com características de crescimento em bovinos da raça Angus - Everling, Dionéia Magda (2012)
The objective of this study was to estimate the (co) variances and genetic associations between the visual scores of conformation and precocity at weaning and at yearling, respectively WC, WP and YC, YP with the characteristics of average daily gain (BWG: from birth to weaning and WYG: from weaning to yearling) and rate of weight gain (BWR: from birth to weaning and BYR: from weaning to yearling) for Angus cattle. The (co)variances components were estimated by multi-traits analysis using an animal model by Bayesian Inference Method, assuming a linear model for average daily gain and for rate of weight gain and a non-linear (threshold) for WC, WP, YC and YP. The a posteriori means for direct heritability were 0.12 (WC), 0.17 (WP), 0.15 (BWG and BWR), 0.17 (YC), 0.19 (YP) and 0.16 (WYG and BYR). The genetic correlation between the weaning and yearling scores with the direct effect for the average daily gain and rate of weight gain traits ranged from -0.05 to 0.60 for conformation and -0.15 to 0.60 for precocity; the genetic correlation of the scores with average daily gain and rate of weight gain presented similar behavior. Therefore, correlated response of equal magnitude is expected for scores, if the selection was directed to average daily gain or rate of weight gain.